Mind Mapping Learning Model and Learning Motivation and its Effect on Aqidah Akhlak Learning Outcomes - Reni Elfida (Ruhama : Islamic Education Journal, 2022)
This study examines the influence of the use of learning media in learning Akidah Akhlak class X MIA in Madrasah Aliyah Negeri 2 Payakumbuh City for the 2021/2022 school year. In the study, researchers used mind mapping learning media to improve the learning skills of students in a relatively open, reflective, critical and active learning mindset and facilitate students to increase creativity in understanding learning materials. First, conducting a scoring of motivational questionnaire sheets and student learning test results in the subject of moral akhlak class X MIA at Madrasah Aliyah Negeri 2 Payakumbuh City. The second converts the score into a value. Third, determine the calculated average (M) of each test sheet. Fourth, group the value of learning motivation and test results of moral academia subjects. fifth, conduct an analysis requirements test. Sixth, test the hypothesis. Seventh, discuss the results of the analysis and conclude the results of the discussion. The results of the study are First, the learning motivation of experimental class learners is in the good category with an average of 91. Second, the learning outcomes of the students of the experimental class with an average score of 80.27 were better than the control class with an average score of 73.81. With a calculated value (8.368) greater than the ttable value (2.68) at the degree of freedom n1+n2-2 (61) and a significant level of 95%.